Cost effectiveness of heptavalent pneumococcal conjugate vaccine in populations of high risk in Colombia - NELSON ALVIS GUZMÁN (Colombia Médica, 2010)
Objective: To estimate the economic impact of the introduction of heptavalent pneumococcal conjugate vaccine (PCV- 7) in high risk populations of Colombia. Methods: A full economic evaluation was done regarding potential introduction of PCV-7. A cost-effectiveness study from the perspective of the third payer was done using a Decision Model. The model considered two alternatives: with and without vaccination. As measurement of results the avoided events were taken [cases, hospitalizations, deaths and Life-Years Saved (LYS)]. In addition the net costs and the incremental cost-effectiveness ratio (ICER) were evaluated. Results: In a cohort of 70 thousand children of under 2 years old in situation of high risk, can generate 532 deaths that would produce a little more than 21 thousand Years of Life Lost (YLL) with costs between 7.7 and 13.3 million dollars. If we vaccinate this same cohort the deaths can be reduced to 355, and the costs of burden of disease would be between 5.7 and 10 million dollars. It is estimated a reduction of 25% of the costs of burden of disease and of 33% of the deaths. In addition the ICER by YLS would be between 590 and 762 dollars. Conclusion: The introduction of the Heptavalent Pneumococcal Conjugate Vaccine in populations of high risk is highly cost effective in Colombia.